Unlocking India's Logistics Potential : The Value of Disaggregated Macroscopic Freight Flow Analysis - Aritua, Bernard; Havenga, Jan; Simpson, Zane; Chiew, Esther Woon Lyn (World Bank, Washington, DC, 2018)
India is one of the fastest growing major economies. However, at 14 percent of gross domestic product, its logistics costs are high relative to the 8 to 10 percent that is typical of most advanced economies. High logistics costs and poor logistics performance impact the competitiveness of the economy on multiple levels: (1) firms deliver less competitive goods and services; (2) consumers pay more than peers for goods; and (3) the cost of achieving improvements in gross domestic product is excessive. The development of a national transport and logistics network to facilitate competitiveness and sustainable development and uplift rural regions will play an increasingly important role in shaping spatial organization in emerging economies. An element that is absent, yet critically important for national logistics issues in emerging economies, is sufficiently detailed freight-flow analysis to facilitate targeted infrastructure investments and enable transformational change to improve national logistics performance. This paper presents the results of a disaggregated macroscopic freight demand analysis developed for India through a hybrid approach, calibrating the modeled input-output matrix and resulting freight flows with data where available. Data was obtained from multiple sources, such as agricultural statistics, national enterprise surveys, a financial performance database of Indian companies, population statistics, and transportation statistics from rail, inland waterways transport, highways, and ports. The model provides evidence for decision making on several levels. Aggregating freight flows enables planners to identify gaps in critical infrastructure and logistics chains. Disaggregated flows support decisions on the location of logistics clusters, maximizing the potential of multimodal transport systems, and designing the distribution and storage networks that underpin the economy.